2022
DOI: 10.3389/fpubh.2022.921226
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Use Artificial Intelligence Methodologies in Health Technology Assessment in Central and East European Countries

Abstract: The aim of this paper is to identify the barriers that are specifically relevant to the use of Artificial Intelligence (AI)-based evidence in Central and Eastern European (CEE) Health Technology Assessment (HTA) systems. The study relied on two main parallel sources to identify barriers to use AI methodologies in HTA in CEE, including a scoping literature review and iterative focus group meetings with HTx team members. Most of the other selected articles discussed AI from a clinical perspective (n = 25), and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…A previous work product of the HTx project, including a literature review and focus group, identified a total of 29 barriers that specifically hinder the use of AI-based evidence in HTA systems in CEE countries ( 3 ). The barriers in that study were categorized as data-related, methodological, technological, regulatory and policy-related, and human-factor-related ( 3 ). The results of the study were used as a basis to select the most important barriers for the CEE countries.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…A previous work product of the HTx project, including a literature review and focus group, identified a total of 29 barriers that specifically hinder the use of AI-based evidence in HTA systems in CEE countries ( 3 ). The barriers in that study were categorized as data-related, methodological, technological, regulatory and policy-related, and human-factor-related ( 3 ). The results of the study were used as a basis to select the most important barriers for the CEE countries.…”
Section: Methodsmentioning
confidence: 99%
“…Artificial intelligence has attracted much attention because of its potential in healthcare to improve access, quality and efficiency (2), but its adoption has been slow due to several factors that are specific to healthcare (e.g., legal and ethical restrictions to accessing patient level data, fragmented databases, interoperability issues with pooling data etc.) (2,3), resulting in a lag of healthcare behind other industries (4). Although AI has been applied in several areas of healthcare, such as more accurate and faster detection, prediction, and diagnosis of diseases (5,6), its use in supporting health policymaking has been limited so far (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations